Kehamilan, Persalinan dan Nifas pada Suku Dayak Sanggau - Evie Trihartiningsih; Novia Karolina; Riani Riani; Rofika Dwi Permata Sari; Romika Romika; Siti Nafizah Rokhimi; Sovia Loren; Sylvinia Crystin Adelia; Sutia Sutia; Veronica P.A.P.S (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
The Dayak Sanggau community practices a number of cultural traditions during pregnancy, childbirth, and the postpartum period, reflecting a blend of spiritual beliefs and medical needs. This study employed a qualitative method with a literature review (library research) approach to explore pregnancy, childbirth, and postpartum practices among the Dayak Sanggau people. The findings identified supportive practices such as spousal involvement and basic check-ups by traditional midwives, as well as potentially harmful practices including non-sterile vaginal examinations, childbirth in the kitchen area, and the use of alcoholic herbal concoctions for infants. The conclusion emphasizes the importance of understanding local culture and integrating medical education so that positive traditional practices can be preserved, while risky ones are minimized through culturally sensitive interventions.